2017
DOI: 10.7448/ias.20.1.21467
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and perceived fairness of option B+ in Malawi: a population‐level perspective

Abstract: Introduction: Policies for rationing antiretroviral therapy (ART) have been subject to on-going ethical debates. Introduced in Malawi in 2011, Option B+ prioritized HIV-positive pregnant women for lifelong ART regardless of the underlying state of their immune system, shifting the logic of allocation away from medical eligibility. Despite the rapid expansion of this policy, we know little about how it has been understood and interpreted by the people it affects. Methods: We assessed awareness and perceived fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…The current study finding was higher than the finding of studies done in Gahanna (25%), Tanzania (35.2%), South Africa (23.1%), and Uganda (30.1%) [9][10][11]22 and lower than the studies done in Malawi (68%). 8 This variation of findings across various studies might be due to cross-cultural limitations of diagnostic tools and reporting biases, differences in socio-economic environments. However, this study finding was comparable to studies done in Hadyia and Mekelle town which reported pregnant women knowledge of PMTCT B + were 59.9% and 56.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study finding was higher than the finding of studies done in Gahanna (25%), Tanzania (35.2%), South Africa (23.1%), and Uganda (30.1%) [9][10][11]22 and lower than the studies done in Malawi (68%). 8 This variation of findings across various studies might be due to cross-cultural limitations of diagnostic tools and reporting biases, differences in socio-economic environments. However, this study finding was comparable to studies done in Hadyia and Mekelle town which reported pregnant women knowledge of PMTCT B + were 59.9% and 56.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was agreed with reports of WHO 2014 and Malawi. 1,8 The possible explanation may be that employment leads to adequate knowledge of PMTCT B + option in a number of ways. When women become unemployed, it is a stressful event that affects their self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the survey suggested that those who stopped ART did so due to their extensive distance from the clinic, having limited transportation, HIV disclosure status, limited education concerning why they were receiving treatment, and others [18] [19] [20]. Pertaining to Option B+ education, a study by Yeatman et al 2017 showed that only 30.7% of women and 21.1% of male partners understood how ART was distributed, and most respondents were unaware that healthy pregnant women were included in Option B+ [21].…”
Section: Tweya Et Al 2014 Conducted a Retrospective Cohort Study In mentioning
confidence: 99%
“…Key findings have centered on the changing HIV treatment context (Yeatman et al. ; Yeatman and Trinitapoli ), fertility preferences (Trinitapoli and Yeatman ; Yeatman, Sennott, and Culpepper ; Yeatman and Sennott ; Sennott and Yeatman ; Trinitapoli and Yeatman ), education and literacy (Smith‐Greenaway ; Frye ), young‐adult relationships (Frye and Trinitapoli ), and family dynamics (Bachan ; Trinitapoli, Yeatman, and Fledderjohann ). A publication list for TLT is available at https://scholar.google.com/citations?user=OFx9oPIAAAAJ&hl=en.…”
Section: Value Of the Datamentioning
confidence: 99%